2021
DOI: 10.3390/ani11041152
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Quality and Safety of Fresh Camel Meat Contaminated with Campylobacter jejuni Using Citrox, Chitosan, and Vacuum Packaging to Extend Shelf Life

Abstract: Camel meat is one of the most consumed meats in Arab countries. The use of natural antimicrobial agents to extend the shelf life of fresh camel meat, control Campylobacter jejuni contamination, and preserve meat quality is preferred. In this study, we determined the antimicrobial effects of using 1% or 2% Citrox alone or in combination with 1% chitosan on the survival of C. jejuni in vitro and on camel meat samples during storage at 4 or 10 °C for 30 days in vacuum packaging. We determined the total viable cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 62 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…The infraspinatus, triceps brachii, longissimus thoracis muscles have significantly lower shear-force (6.3-6.7 kg) values than semitendinosus, semimembranosus, and biceps femoris muscles (9-12.9 kg), which might be due to less connective tissue. Suliman et al (2019) reported a similar result.…”
Section: Tendernessmentioning
confidence: 60%
See 3 more Smart Citations
“…The infraspinatus, triceps brachii, longissimus thoracis muscles have significantly lower shear-force (6.3-6.7 kg) values than semitendinosus, semimembranosus, and biceps femoris muscles (9-12.9 kg), which might be due to less connective tissue. Suliman et al (2019) reported a similar result.…”
Section: Tendernessmentioning
confidence: 60%
“…Similarly, Jouki and Khazaei (2012), using an anoxic MAP (60% CO 2 + 40% N 2 ) combined with refrigeration storage (4°C) have obtained significant improvement in physicochemical and sensory properties of camel meat within three weeks of storage. Recently, Yehia et al (2021) reported that the use of combined natural biopreservative agents (Citrox and chitosan) can be a promising tool to control Campylobacter jejuni growth and to preserve packaged camel meat even at abuse refrigeration (10°C) storage. A combination of essential oils (EOs) components like carvacrol, thymol or cinnamaldehyde with the yogurt-based marinade exerts a lethal effect against Escherichia coli O157: H7 and Salmonella spp.…”
Section: Maqsood Et Al (2016)mentioning
confidence: 99%
See 2 more Smart Citations
“…The authors reported that 2.5% concentration of each nisin and gingerol decreased the level of cadaverine, tyramine, and spermidine to belowdetectable levels. Furthermore, addition of chitosan in combination with citrox was reported to significantly improve various sensory parameters such as colour, odour, flavour, taste, as well as overall acceptability measured using a hedonic scale [90].…”
Section: Effect Of Pretreatmentsmentioning
confidence: 99%